Crop-livestock interactions and livelihoods in the Gangetic Plains of West Bengal, India: findings from a scoping study - Erenstein, Olaf; Varma, A.; Thorpe, W.R.; Singh, J. (2010)
The research and development community faces the challenge of sustaining crop productivity gains, improving rural livelihoods and securing environmental sustainability in the Indo-Gangetic Plains. This calls for a better understanding of farming systems and of rural livelihoods, particularly with the advent of, and strong advocacy for, conservation agriculture and resource-conserving technologies. The paper summarizes the findings from a scoping study to assess crop-livestock interactions and rural livelihoods in the Gangetic Plains of West Bengal, drawing from a village survey in three districts (Malda, Nadia and W Medinipur) and secondary data. The rice-cattle based rural livelihoods are in stark contrast with those in the western Indo-Gangetic Plains, whereas the state’s high human and livestock pressure and high poverty pose particular challenges to sustainable intensification and poverty reducing agricultural growth – particularly in the more remote districts. Strengthening the client orientation and productivity of the agricultural R&D community will be central to improving livelihoods and more sustainably using natural resources – and research on crop-livestock interaction serves as a good entry point for that process.